The Analysis of imposition, deposit and reporting of value-added tax by PT. Seimitsu Diagnostics - Lestari, Ary; Yusrizal, Yusrizal; N, Lukman Hakim; Susilo, Danang Djoko; Rachmany, Hasan (Universitas Negeri Makassar, 2020)
The Taxation Law in Indonesia refers to Self-Assessment System, which is giving trust to the taxpayer to calculate, deposit and report by themselves about the amount of tax owed according to the regulation of taxation law. While the purpose of writing this thesis generally is to know about the imposition, deposit and reporting of value-added tax by PT. Seimitsu Diagnostics has appropriated with the provision of value added tax law within the applicable taxation enforcement rules and to know how PT. Seimitsu Diagnostics to overcome the obstacle encountered in implementing the value-added tax collection and to know theÂ effort that have been taken to overcome the problems. The writer does this research by collecting data and processing method and analysing data. The writer does the research in the company to get the data and collecting them. The obstacle is about the output tax difference always bigger than the input tax, so it can cause there are the amount of underpaid taxes and the company is considered to be negligence in the deposit and report the underpaid taxes on every tax period or tax year so according to article 8 section (2) Law number 6 Year 1983 about the General Condition and tax procedure of the company got penalty to a 2% interest in a month for the underpayment amount.Â